Manipulation of a quasi-natural cell block for high-efficiency transplantation of adherent somatic cells - H.J. Chung (Brazilian Journal of Medical and Biological Research, 2015)
Recent advances have raised hope that transplantation of adherent somatic cells could provide dramatic new therapies for various diseases. However, current methods for transplanting adherent somatic cells are not efficient enough for therapeutic applications. Here, we report the development of a novel method to generate quasi-natural cell blocks for high-efficiency transplantation of adherent somatic cells. The blocks were created by providing a unique environment in which cultured cells generated their own extracellular matrix. Initially, stromal cells isolated from mice were expanded in vitro in liquid cell culture medium followed by transferring the cells into a hydrogel shell. After incubation for 1 day with mechanical agitation, the encapsulated cell mass was perforated with a thin needle and then incubated for an additional 6 days to form a quasi-natural cell block. Allograft transplantation of the cell block into C57BL/6 mice resulted in perfect adaptation of the allograft and complete integration into the tissue of the recipient. This method could be widely applied for repairing damaged cells or tissues, stem cell transplantation, ex vivo gene therapy, or plastic surgery.